Risk Factors and Outcomes of Patients Requiring a Permanent Pacemaker After Aortic Valve Replacement in the United States. Issue 8 (22nd June 2016) - Robich, Michael P.; Schiltz, Nicholas K.; Johnston, Douglas R.; Mick, Stephanie; Krishnaswamy, Amar; Iglesias, Rodrigo A.; Hang, Dustin; Roselli, Eric E.; Soltesz, Edward G.
Abstract: Introduction: The need for permanent pacemaker implantation (PCM) following surgical aortic valve replacement (SAVR) is uncommon but can lead to increased hospital resource utilization. Using nationwide data, we sought to (1) identify hospital, patient, and procedure‐level risk factors for PCM after SAVR and (2) determine incremental resource utilization. Methods: We identified 659, 692 patients from the Nationwide Inpatient Sample database who underwent SAVR with or without coronary artery bypass grafting (CABG), mitral valvuloplasty (MVr), or mitral valve replacement (MVR) between 1998 and 2009. Patients with pre‐existing pacemakers, a concomitant Maze procedure, or endocarditis were excluded. Multivariable regression analysis and propensity matching were used for comparisons of outcomes and costs. Results: Overall prevalence of PCM was 5.1% (n = 34, 020; SAVR alone, 4.8%; SAVR + CABG, 4.6%; SAVR + MVr, 7.7%; SAVR + MVR, 10%). Important risk factors for PCM after SAVR were coexisting comorbidities, older age, and addition of mitral valve surgery. Hospital volume and teaching status, location, race, and sex were not associated with PCM. Among matched pairs, patients requiring PCM had lower in‐hospital mortality (3.1% vs. 6.4%, p < 0.001) but longer median length of stay (12 vs. 9 days, p < 0.001) and higher hospital costs (50, 000 vs. 37, 000, p < 0.001), and they were less likely to be discharged home (33% vs. 36%, p < 0.001). Factors associated with later PCM (postoperative day ≥6) included SAVR + MVR, female sex, fewer comorbidities, northeastern region, and higher hospital volume. Median hospital costs were greater (57, 000 vs. 48, 000, p < 0.001) among patients whose pacemakers were implanted later. Conclusions: PCM following SAVR is associated with lower hospital mortality, but increased cost and length of stay. doi: 10.1111/jocs.12769 (J Card Surg 2016;31:476–485)